Relationship between serum cystatin-C and urinary neutrophil gelatinase-associated lipocalin in septic children - Jose Mandei; Elisa Iskandar; Adrian Umboh; Hesti Lestari (Indonesian Pediatric Society, 2015)
Background Sepsis may lead to acute kidney injury (AKI)in patients treated in pediatric intensive care units (PICU).Currently, serum creatinine is used as a biomarker for thediagnosis of AKI. However, it is not a sensitive nor specifictest for AKI. The scarcity of biomarkers leads to delays in thediagnosis and treatment of AKI. Serum cystatin-C (sCys-C)and urinary neutrophil gelatinase-associated lipocalin (uNGAL)are potential biomarkers that look promising for early diagnosisof AKI.Objective To identify the relation of cystatin-C and NGAL inchildren with sepsis.Methods Serum cystatin-C and uNGAL were measured onseptic patients aged one month to 12 years. The diagnosesof sepsis were based on the 2002 International Pediatric SepsisConcensus. Patients were admitted to the Pediatric IntensiveDepartment of the Prof. Dr. R. D. Kandou Hospital, Manadofrom January to June 2013. The exclusion criteria werepatients with trauma, burns, severe dehydration, malnutrition,obesity, and history of renal diseases. Data analyses includeddescriptions for the characteristic data and Pearsonâ€™s coefficientcorrelation. A P value of 0.05 was considered to be statisticallysignificant. Data were analyzed with SPSS software for Windowsversion 21.Results Thirty-eight patients met the inclusion criteria, of whom23 were male and 15 were female. Their mean age was 22.6 (SD32.24) months, with overweight in 2 children, good nutrition in25 children, and under nutrition in 11 children. An increasedlevel of sCys-C was found in 22 children and an increased levelof uNGAL was found in 19 children. Serum cystatin-C wassignificantly correlated to uNGAL in septic patients (r=0.614;P<0.01).Conclusion There is a positively correlated relationship betweensCys C and uNGAL in septic children. Increased sCys C isÂ associated with increased uNGAL in septic children.